On the Very Idea of Unified Sociology: Harvard and Columbia - Balon, Jan (Teorie vědy / Theory of Science, 2011)
On the Very Idea of Unified Sociology: Harvard and Columbia Abstract: The article concentrates on the historical context of American sociology’s development in the period between 1930 and 1965, which is here associated with a specific project of the field’s unification elaborated at Harvard University and Columbia University. It is argued that the idea of unified sociology is worked in the very project of American sociology as a science and found its genuine expression in the efforts to reach "objectivity and coherence" of sociological thought/knowledge. It also distinctly formed the professional identity of the discipline. It was expected that the scientific integrity would be achieved by means of securing the continuity of theory and practice, which was to provide a general methodological pillar for cumulative research. The historical contextualization of this formative period studies how the very idea of unified sociology affected both theoretical and methodological perspectives within the discipline and also the possibility of its integrated research agenda. O samotné myšlence jednotné sociologie: Harvard a Columbia Abstrakt: Článek se zaměřuje na historický kontext vývoje americké sociologie v období mezi lety 1930-1965, jež je spojeno se specifickým projektem sjednocení oboru rozpracovaným na Harvardské a Kolumbijské univerzitě. Samotná myšlenka jednotné sociologie je neoddělitelně vpletena do celého projektu americké sociologie jako vědy a své „čisté" vyjádření nalezla v úsilí prokázat „objektivitu a koherenci" sociologického myšlení/vědění. Zcela zřetelně také formovala profesní identitu oboru. Prostředkem zajištění vědecké integrity bylo především zajištění kontinuity teorie a praxe, ježby založilo a o něž by se mohlo opírat pevné metodologické „sebevědomí". Historická kontextualizace tohoto formativního období si klade za cíl sledovat, nakolik myšlenka sjednocené sociologie ovlivnila teoretické a metodologické perspektivy v rámci oboru i vlastní představy o možnosti jeho integrované výzkumné agendy.